Polycystic ovary syndrome and its possible therapeutic approaches: A literature review (Research, Society and Development, 2023)
Polycystic ovary syndrome (PCOS) is a disease characterized by multiple cysts in the ovaries that generate heterogeneous alterations in various aspects of the patient's life. Examples of these alterations include hormonal imbalances, irregular menstrual cycles, and manifestations of weight gain, acne, reproductive difficulties, and hirsutism. As a result, the diagnosis and treatment of PCOS become multifaceted, given the complexity of the syndrome. This present study aims to address the psychosocial implications in the patient's life and analyze the currently available therapeutic management options described. It is a literature review of the integrative type, based on scientific productions from databases such as the National Library of Medicine (PubMed), Virtual Health Library (BVS), Google Scholar, and Scientific Electronic Library Online (SciELO), as well as terminologies registered in the Health Sciences Descriptors (DeCS). The publications included in the review span from 2013 to 2023. Through the significant impacts caused in the lives of patients with PCOS, it was concluded that the therapeutic management options in the market are heterogeneous, just like the entire polycystic ovary syndrome.